Disparity analysis and prognostic value of pretreatment whole blood Epstein‐Barr virus DNA load and Epstein‐Barr encoding region status in lymphomas: A retrospective multicenter study in Huaihai Lymphoma Working Group. Issue 2 (24th September 2021) - Shen, Ziyuan; Hu, Lingling; Yao, Mingkang; He, Chenlu; Liu, Qinhua; Wang, Fei; Gu, Weiying; Wang, Ying; Dong, Manyu; Zhu, Taigang; Yin, Ting; Li, Fei; et al.
Abstract: Elevated Epstein‐Barr virus (EBV) DNA load is common in lymphomas. However, it remains unclear whether the disparity in viral load and its prognostic value in lymphomas are correlated with Epstein‐Barr encoding region (EBER) status. In this retrospective multicenter study, we collected the data of pretreatment whole blood EBV DNA (pre‐EBV DNA) and EBER status and evaluated their disparity and prognostic values in lymphomas. A total of 454 lymphoma patients from December 2014 to August 2020 were retrospectively retrieved. Mann‐Whitney U  test, Kruskal‐Wallis test and Bonferroni's adjustment were used to explore the disparity of EBV DNA and EBER status in lymphomas. Time‐dependent receiver operating characteristic analysis and MaxStat analysis were used to determine optimal cutoff points of pre‐EBV DNA load. Univariable and multivariable Cox proportional hazards models were established for the estimation of prognostic factors. The positive rate of EBV DNA in natural killer T‐cell lymphoma (NKTL) patients was higher than that in diffuse large B‐cell lymphoma (DLBCL), follicular lymphoma (FL) and Hodgkin lymphoma (HL) patients, and the median positive pre‐EBV copy number of NKTL was also higher than that of FL and DLBCL. EBV DNA could clearly distinguish the prognosis of DLBCL, NKTL, HL and peripheral T‐cell lymphoma, and the integration of EBER status and EBV DNA could differentiate the prognosis of HL patients. Multivariable results revealed that pre‐EBV DNA load had an effect on the prognosis of NKTL, FL and DLBCL. The status of pre‐EBV DNA and EBER were disparate. Whole blood pre‐EBV DNA predicted the prognosis of lymphomas, and the combination of EBV and EBER status could differentiate the prognosis of HL. Abstract : What's new? Elevated plasma levels of Epstein‐Barr virus (EBV) are common in lymphoma and may be linked to prognosis. EBV DNA levels prior to treatment, which are detected by Epstein‐Barr encoding region (EBER) in situ hybridization, may be of particular prognostic relevance. Here, the authors evaluated data on pretreatment EBV (pre‐EBV) status and disparities in EBER status and prognostic values among lymphoma patients. Analyses show that whole‐blood pre‐EBV DNA is prognostic for lymphoma. In Hodgkin lymphoma, combined EBV and EBER status successfully differentiated prognosis. The findings suggest that EBV DNA monitoring is valuable for the detection and treatment of EBV‐associated lymphoma.